Pengaruh senam aerobik terhadap kebugaran jasmani - Kevin Waldo; Syafaruddin Syafaruddin; Wahyu Indra Bayu; Soleh Solahuddin (STKIP PGRI Jombang, 2022)
Gymnastics is a very good sport for the body and physical fitness if we do the exercise correctly. This study aims to 1) Improve physical fitness using aerobic exercise, 2) Give effect to the Gymnastics Club KOPKI Jambi City, 3) Provide aerobic exercise treatment to improve physical fitness, 4) Provide aerobic exercise treatment and gender to distinguish the increase in physical fitness. 5) Seeing gender differences to be able to distinguish levels of physical fitness. This experimental study uses a 2x2 factorial design to determine the effect of variables with various main factors, and the combination of variable levels and the effect of interactions between factors on physical fitness levels. With a total sample of 30 men and 30 women aged 20-29 years. Based on the results of the research conducted, the male gender for low impact got the initial test score of 507.7 for the final test of 560.8 then the male high impact on the initial test of 548.2 for the final test of 628, Second, the female gender on the initial low impact test was 439.6 for the final test of 521.4 on the high impact female initial test of 496.9 and the final test was 583.9. Based on the results of research and discussions that have been carried out, it can be understood that: (1). Overall, there is an increase in physical fitness (Vo2Max) at the Jambi City KOPKI Club as evidenced by the significance value smaller than the 0.05 level as shown in the Hypothesis Testing table. (2). There are differences in the increase in physical fitness (Vo2Max) to aerobic exercise and gender at the KOPKI Gymnastics Club Jambi City seen in the number of test results for each group.